Descending thoracic aortic homograft for superior vena caval translocation in the Warden procedure: Report of six cases. Issue 12 (8th October 2022) - Said, Sameh M.; ElBokl, Amr; Brown, Nicholas M.; Narasimhan, Shanti
Abstract: Background: Warden procedure has been described for repair of partial anomalous pulmonary venous connections inserted high into the superior vena cava. In the current report, we describe a new modification. Methods: A total of six patients (five females, 83%) with a mean age of 18.8 ± 10.8 years, underwent a modified Warden procedure with a descending thoracic aortic (DTA) homograft connected to the free wall of the right atrium, rather than to the right atrial appendage in the period between June 2021 and July 2022. Results: All patients had evidence of enlarged right‐sided cardiac chambers. Two patients had intact interatrial septum (33.3%), while three patients had sinus venosus (50%) and one had secundum atrial septal defects (16.7%). The procedure was performed via minimally invasive right thoracotomy in half of the patients. Patients were extubated in the operating room or soon after. No early mortality or reoperation. One patient required concomitant aortic root replacement and one needed repair of anomalous left upper pulmonary vein connection to the left innominate vein. Follow‐up was complete in all patients with a mean of 6.2 ± 4.6 months. No late mortality or reoperation. All patients were discharged on antiplatelet therapy. Follow‐up imaging studies showed satisfactory repair with widely patent superior vena caval and pulmonary venous pathways. Conclusions: The use of DTA homograft to facilitate superior vena caval translocation in the modified Warden procedure appears to be beneficial as it decreases tension on the anastomosis and avoids the need for anticoagulation.